Vasculitis with renal involvement in mixed essential cryoglobulinemia - Islam Bhatti, Sajid; Waqar, Tajammul; Younas, Shafique; German, Sidra (Pakistan Journal of Kidney Diseases, 2024)
Cryoglobulins are proteins that precipitate individual’s serum or plasma at temperatures lower than 37°C. It could be due to immunoglobulin and complement component or immunoglobulin alone. They produce physical finding of ischemia, inflammation in areas of low temperature (skin, ear lobes, nose and fingers), and of high protein concentration (glomeruli) especially at high concentration in plasma. We report here a case of middle age male who presented with worsening of pedal edema, high blood pressures and shortness of breath. On workup found to have nephrotic range proteinuria. Renal biopsy done which showed mesangiocapillary glomerulonephritis with hyaline thrombi. After biopsy report cryoglobulins were sent which turn out to be positive and patient was subjected to immunosuppression to which he responded well. However; we could not find out the cause of cryoglobulinaemia hence we labeled it as mixed essential cryoglobulinaemia.